Giyera sa Droga (War on Drugs): An application of the Theory of Planned Behaviour to the influence of negative word-of-mouth communication to the tourists’ intention to visit the Philippines - Arboleda, Quiarra Pauline M.; Cano, Fervi Mae C.; Chu, Carla Sarahmina G.; Rosario, Christine Kei L. Del; Dimalanta, Nicole E.; Macalincag Jr., Rosle M.; Andalecio, Avi Ben Pestañas (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2023)
War on drugs campaign commenced in the Duterte Administration in 2016. The campaign resulted to worldwide criticisms which spread negative word-of-mouth about the Philippines. The study applied the Theory of Planned Behaviour (TPB) by Ajzen and Fishbein (1991) to test the negative word-of-mouth (WOM) communication regarding war on drugs to tourists’ intention to visit the Philippines. Structural Equation Modelling was utilized to determine the relationship among the three factors of TPB namely, Attitude, Subjective Norm, and Perceived Behavioural Control to tourist intention. The data was collected from 242 foreign passport holders and through an interview conducted with the Department of Tourism (DOT). The result of the study reveals that Attitude does not affect tourist intention to travel. On the other hand, Subjective Norm has the strongest influence on tourist intention followed by Perceived Behavioural Control but does not necessarily affect their decision-making behaviour towards visiting the Philippines regardless of the campaign.